Pengaruh Independensi dan Bisnis Ecommerce terhadap Kebutuhan Jasa Audit E-commerce - Gusma Indah; Paramita Srida Yanti; Sri Hajratul (JURNAL PUNDI, 2020)
Auditors who can help e-commerce businesses in improving business quality. The use of audit services in e-commerce business gives a good influence for the needs of audit services.. In order for the business to use insurance services to protect all data consumers who shop business size will also affect the use of large-scale e-commerce audit services for businesses in the use of e-commerce audit services. Therefore, the purpose of this study is to find out whether the influence of auditor expertise and e-commerce business has a significant influence on audit services.